PEMBINAAN MASYARAKAT MULTIKULTURAL DALAM MENINGKATKAN INTEGRASI BANGSA - Eli Karliani (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstrak The elucidation ofmulticultural society in Palangka Raya is needed to increase the integration of the nation because the society of Palangka Raya is variety in ethnic, religion, language, culture, and individual characteristic. By using the observation, interview, documentation and literature study, it revealed the deeper problem where can be found the actual data. To govemment is by the understanding of ethnic values and the cultural relativism, through Communication Forum of Cross-Ethnic (FKLE) and Communication Forum ofReligions (FKUB), old customs in orderliness of Palangka Raya city's law No. 18 in 2007 about Kedamangan. In the ethnic groups, by having the cultural collaboration as the form of cultural assimilation, the exchange ofthe village headman with the customs figure from each ethnic, and by adaption process through the motto when in rome do as the romans do. In schooi the subject of cross cultural understanding and multicultural values has been inserted in the religion subject, civic education, and Indonesian language. In family, by inserted the religious values and humanity will eliminate the steorotive and the fanatism ethnic or religion.